P-343 Metformin reduces endometrial implants and improves fertility in a mouse model of endometriosis. (30th June 2022) - Neto Cerqueira, A.C; Rodrigues, A.R; Gouveia, A.M; Almeida, H; Neves, D
Abstract: Study question: Could endometriosis-associated infertility be mitigated by metformin? Summary answer: Metformin treatment restored fertility to control rates in endometriosis-induced mice that present lower fertility. Endometrial implants presented a reduction in size with metformin treatment. What is known already: Endometriosis is an inflammatory disease characterized by estrogen-dependent ectopic growth of endometrium causing pain and infertility. Hormone-based medication prescribed need to be interrupted when women intend to conceive. Corroborating observations in women, endometriosis decreases oocyte quality and pregnancy success in rodents. Thus, animal models of endometriosis constitute a valuable tool to elucidate the pathophysiology of the disease and putative therapies. Besides lowering glycaemia, metformin down-regulates estrogen secretion, inflammation and oxidation. Metformin can be safely used before and during pregnancy, it is currently used in gestational diabetes. Metformin has shown to induce regression of endometrial implants in an endometriosis rat model. Study design, size, duration: B6CBA/F1 female mice were randomly divided in groups and subjected to treatment: 1-Endometriosis(E) (n = 20); 2-Sham-operated(S) (n = 12); 3-Endometriosis with metformin(EM) (n = 20); 4-Sham-operated with metformin(SM) (n = 20). Endometriosis was surgically induced by heterologous transplantation of endometrium from one donor in receptors from the same strain mice. Implants were confirmed and monitored by ultrasound. 50mg/kg/day of metformin was orally administrated during 3 months to Groups 3 and 4. Half of mice in each group were mated to fertility study. Participants/materials, setting, methods: Endometrial implants were monitored at 3 timepoints during the experiments. Fertility rates were assessed by the average number of fetuses in each group. Histological characterization of eutopic and ectopic endometrium was performed by H&E and Masson's trichrome staining. Immunofluorescence for PCNA and CYP17A1 proteins, markers of cell proliferation and estrogen secretion, respectively were performed. Western blotting quantification for these proteins is in course. Statistical analysis was carried out and significant differences were considered for p < 0.05. Main results and the role of chance: A decrease of 30% of fertility rate was verified in mice with endometriosis (p = 0, 01); treatment with metformin was able to revert this decrease (p = 0, 04). Interestingly, no differences in fertility were found in sham-operated mice under metformin treatment relatively with those of group 2 (p = 0, 16). No biometrical differences were found between mice with endometriosis receiving metformin and those that do not receive the drug. Implants size were reduced by metformin treatment. Histological similarities were observed between the ectopic tissue and uterus. It is possible to observe that the ectopic endometrium layer is thinner in the EM group compared with the E group. PCNA and CYP17a labeling was present in the same cells of eutopic and ectopic endometrium, with an apparent lower number in the ectopic tissue in the EM group. In addition, in untreated animals, the cavity of ectopic tissue has more flaking cells than in animals with metformin treatment. In sum, metformin seems to have a positive role in the control of cell proliferation and estrogen production of ectopic endometrium. We postulate that these findings owes to a metformin-mediated decrease of oxidative imbalance and inflammatory response, induction of regression of endometriomas and regulation of oestrogen secretion. Limitations, reasons for caution: Extrapolation of data from animal models to human needs caution, considering that endometriosis pattern differs between species. Also, further investigation, focused in identification of molecular targets of metformin and molecular pathways activated in endometriosis, is needed and in course. Wider implications of the findings: With these results, we suggest metformin as a novel and safe strategy to mitigate endometriosis-related oxidative stress and indeed could be used as a valid pharmacological approach to ameliorate endometriosis-associated infertility Trial registration number: Not applicable